LA PARADOJA AMBIENTAL EN EL POSCONFLICTO COLOMBIANO (2019)
The Colombian State by implementing the peace agreements must guarantee sustainable development, since the construction of peace cannot transmute as a threat to the environment. The relevance of the environment in the construction of peace is undeniable since the armed conflict takes place amidst the exuberant biodiversity that the country has, being one more victim of armed groups outside the law, drug trafficking, corruption, among others. Biodiversity and ecosystems are the natural wealth that enable economic growth and social development to flourish, but unfortunately these are threatened by unsustainable practices that deplete these ecosystems, even irreversibly. To achieve sustainable development, all interested parties must be involved: private agents, the government, civil society, among others; to understand the value of biodiversity and thus establish policies and investments that create new benefits. This is an opportunity for Colombia to improve its economy around natural resources, since it is undeniable that the armed conflict has caused damage to the environment. The paradox, regarding environmental protection in the post-conflict, indicates that, not because peace agreements are implemented, protection of natural resources is automatically generated; otherwise, experiences such as the one of the Republic of the Congo allow observing that, if the challenges in the resolution of conflicts regarding the environment are ignored, it could lead to further destroying the nation’s natural heritage. Therefore, it is important to analyze the relationship between peace and environment, and to achieve this it is necessary to study other scenarios at the international level; as well as what treatment will be provided in the peace agreements to the areas occupied by the insurgent groups, and finally the role of the legal offices in the post-conflict.